Biomimetic in situ Regeneration of Cofactors NAD(P)+ and NAD(P)H Models Hantzsch Esters and Dihydrophenanthridine - Du, Wangming; Yu, Zhengkun (Synlett, 2012)
Biomimetic recycling of the expensive cofactors NAD(P)H/NAD(P)+ and their models is a promising area in bio-inspired synthesis. This paper highlights the recent advances in the in situ regeneration of the oxidized cofactors NAD(P)+ through oxidation of cofactors NAD(P)H in the presence of an alcohol dehydrogenase by means of dioxygen and a synthetic Fe(III) porphyrin as a biomimetic NAD(P)H oxidase or flavin as catalyst, and biomimetic in situ regeneration of the expensive NAD(P)H models Hantzsch esters (HEH) and 9,10-dihydrophenanthridine (DHPD) by transition-metal and chiral Brønsted acid catalyzed relay asymmetric hydrogenation.1. Introduction2. Biomimetic in situ Regeneration of NAD(P)+3. Biomimetic in situ Regeneration of Hantzsch Esters (HEH)4. Biomimetic in situ Regeneration of Dihydrophenanthridine (DHPD)5. Future Perspective
Keywords: biomimetic; regeneration; asymmetric hydrogenation; Hantzsch esters; dihydrophenanthridine